2007
DOI: 10.1080/10641950601146574
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiovascular Disease in Women with a History of Pregnancy Complicated by Preeclampsia or Intrauterine Growth Restriction

Abstract: Preeclampsia or IUGR may represent an early marker for increased risk for early cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 35 publications
(48 reference statements)
9
102
2
5
Order By: Relevance
“…26,49 Furthermore, previous studies have showed a decreased nocturnal serum melatonin in coronary heart disease and during acute myocardial infarction. 50,51 This approach raises new questions regarding the mechanism of endothelial dysfunction in preeclampsia and suggests that melatonin might be somehow involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,49 Furthermore, previous studies have showed a decreased nocturnal serum melatonin in coronary heart disease and during acute myocardial infarction. 50,51 This approach raises new questions regarding the mechanism of endothelial dysfunction in preeclampsia and suggests that melatonin might be somehow involved.…”
Section: Discussionmentioning
confidence: 99%
“…51 In addition, the non-dipping pattern of circadian BP has been associated with a large increase in cardiovascular morbidity, reflecting an increased risk of target organ damage. 54 Our results showed a decreased melatonin secretion in women with a recent history of preeclampsia and nocturnal hypertension.…”
Section: Daytimementioning
confidence: 99%
“…Among women with preeclampsia, common cardiometabolic risk factors, such as elevated BP, cholesterol, and HOMA‐IR (Homeostatic Model Assessment of Insulin Resistance) scores, become evident as early as within the first year postpartum 71. This suggests that early screening and intervention for these modifiable risk factors may be an effective prevention strategy, although this has never been directly tested.…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 99%
“…2,3,13,14,22 Even the 10-year CVD risk in women with a history preeclampsia is significantly higher with an odds ratio of 1.31 according to the Framingham risk score. 23 Therefore, in our study, the presence Data are presented as number and percentage.…”
Section: Discussionmentioning
confidence: 99%
“…12 For preeclampsia and fetal growth restriction, previous studies on postpartum CVD risk factors revealed a higher prevalence of multiple modifiable risk factors for CVD within the first year after delivery. 5,13,14 However, to date this has not been separately studied for women with previous placental abruption. In this study, we assessed common CVD risk factors in women with a history of placental abruption at 6 to 12 months after delivery, in comparison with a control group of women with a history of only uneventful pregnancies.…”
mentioning
confidence: 99%